Fatwa and the making and renewal of Islamic law: from the classical period to the present - Awass, Omer (Cambridge University Press, 2023)
"Examines the formation, history, and transformation of the Islamic legal discourse and institutions through the lens of a particular legal practice: the issuance of fatwas (legal opinions). Informed lay readers and scholars alike will gain from it an appreciation about the development of the Islamic legal system and its particular legal practices"--